Instruments for measurement of the quality of life of patients infected with HCV virus - Sierpińska, Lidia (Journal of Education, Health and Sport, 2017)
Introduction. Hepatitis C is an important medical and social problem inPoland and worldwide. Among the main tasks of a nurse and physician in the care of this group of chronically ill patients is an improvement in the quality of their life. While assessing the quality of life the essential issue is the level of health, from both the objective and subjective aspects. These tasks may be reliably performed only by means of appropriately selected research methods and instruments. Objective. Presentation of research instruments for investigating the quality of life of patients with the diagnosis of hepatitis C. Materials and method. General and specific research instruments for the assessment of the quality of life were analyzed based on Polish and international literature. Results. Studies of the quality of life of patients with hepatitis C enable recognition of the types of specific problems occurring in their daily functioning. The instruments most frequently used by researchers include the following questionnaires: SF-36, HUI (Health Utility Index), NHP (Nottingham Health Profile), EQ-5D (Quality of Life Questionnaire). The specific tool for the assessment of the quality of life of patients with chronic liver disease due to HCV infection is the questionnaire CLDQ–HCV (Chronic Liver Disease Questionnaire — Hepatitis C). The results of the study provide opportunities for the improvement of the quality of life of these patients by the reorganization of medical, psychological, social and rehabilitation care, which usually lasts for the rest of life. Conclusions. The presented instruments for the assessment of the quality of life of patients with the diagnosis of hepatitis C will allow the researchers recognition of the specific aspects of functioning of these patients in the bio-psycho-social sphere.